2017
DOI: 10.19027/jai.16.2.136-143
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of different levels diets protein for growth performance of Clarias sp. fry cultured in biofloc-based system

Abstract: The study was conducted to evaluate the performance of catfish fry grown using different dietary protein levels in the biofloc-base aquaculture system. Experiments using a completely randomized design, consisted of four treatments and three replications. The treatment consisted of: protein 38% (A), 34% protein (B), 30% protein (C), and protein 26% (D). Catfish with initial weight of 0.83±0.01 g and length of 4.64±0.04 cm were cultured in 60 L tank with density of 90 fish each tank for 35 days. Inoculation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…production, farmers in the hatchery generally feed the fry on high-protein diets in the range of 38-40% to reach the maximum output. This is costly to the farmer and does not match the low selling prices of the fish fry [8]. Since bioflocs can serve as alternative nutritive sources for the reared aquatic species, Tacon et al [61] suggested that bioflocs might also permit the use of lower feed rations and a reduction in the use of costly feed ingredients.…”
Section: Dietary Protein Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…production, farmers in the hatchery generally feed the fry on high-protein diets in the range of 38-40% to reach the maximum output. This is costly to the farmer and does not match the low selling prices of the fish fry [8]. Since bioflocs can serve as alternative nutritive sources for the reared aquatic species, Tacon et al [61] suggested that bioflocs might also permit the use of lower feed rations and a reduction in the use of costly feed ingredients.…”
Section: Dietary Protein Reductionmentioning
confidence: 99%
“…Zhao et al [78] also found that a 20% decrease in DP did not negatively affect the growth performance of mirror cap (Cyprinus carpio specularis) reared in a BFT polyculture system. Khasanah et al [8] demonstrated that 34% DP (C/N ratio 15) can replace 38% DP in catfish (Clarias sp. 4-5 cm) fry reared in a BFT system for 35 days.…”
Section: Dietary Protein Reductionmentioning
confidence: 99%
See 1 more Smart Citation